Electricity-conducting and heat-conducting electromagnetic shielding composite material and preparation method thereof

By silane modification of graphene nanosheets and combining polymer materials, using a three-dimensional porous structure design, the problem of difficulty in achieving conductivity, thermal and electromagnetic shielding at the same time in existing composite materials is solved, and a high-performance conductive thermal electromagnetic shielding composite material is realized.

CN119708846APending Publication Date: 2025-03-28SOUTHERN UNIVERSITY OF SCIENCE AND TECHNOLOGY +1

Patent Information

Application Number
CN202411716844.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult for existing composite materials to achieve good electrical conductivity, thermal conductivity and electromagnetic shielding properties at the same time, especially under low filling loads, and there are problems with interface compatibility and mechanical properties.

Method used

The graphene nanosheets are modified by a silane modifier, combined with the first and second polymer materials, and a three-dimensional porous structure and filler network design are used to realize the preparation of conductive thermoelectric electromagnetic shielding composite materials.

Benefits of technology

It has achieved a composite material with high thermal conductivity, electrical conductivity and electromagnetic shielding properties under low filling amounts, with an in-plane thermal conductivity of 9.86W/mK, an out-of-plane thermal conductivity of 7.26W/mK, an electrical conductivity of 1560S/m, and an electromagnetic shielding effect of 78.6dB, meeting the requirements of aerospace equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708846A_ABST
    Figure CN119708846A_ABST
Patent Text Reader

Abstract

The invention discloses an electric conduction and heat conduction electromagnetic shielding composite material and a preparation method thereof, and relates to the field of composite materials, and the preparation method of the electric conduction and heat conduction electromagnetic shielding composite material comprises the following steps: modifying graphene nanosheets by using a silane modifier; adding the obtained silane modified graphene nanosheet, a first polymer material and soluble particles into an organic solvent to obtain a mixed solution; placing the mixed solution in a mold with a preset shape, drying, placing the obtained material with the preset shape in a hot water bath, and cleaning to obtain a three-dimensional porous material; pouring a second polymer material into the pore channels of the three-dimensional porous material, and curing to obtain the electric-conduction and heat-conduction electromagnetic shielding composite material, the soluble particles are soluble in water but not soluble in the organic solvent. The electric conduction and heat conduction electromagnetic shielding composite material provided by the invention has good electric conduction, heat conduction and electromagnetic shielding performance, and has an isotropic heat conduction effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of composite materials, and in particular to an electrically conductive, thermally conductive, electromagnetic shielding composite material and a preparation method thereof. Background Art

[0002] The rapid progress of electronic information technology has promoted the development of cutting-edge fields such as artificial intelligence, 5G / 6G communications, and new energy transportation. At the same time, it has also put forward higher requirements for the integration, power density, and high frequency of electronic components. High integration and high frequency mean that the interior of electronic components is more compact and the electromagnetic interference between components is intensified. Therefore, more effective electromagnetic shielding materials or methods must be used to ensure the safety and signal integrity of these devices. In addition, the increase in power density and space limitations lead to the accumulation of heat, which seriously damages the service life and reliability of the equipment. This phenomenon places strict requirements on the heat dissipation capacity of electronic components. At the same time, in order to achieve high-speed signal transmission, better conductivity is also required. Therefore, the development of composite materials with good electrical conductivity, electromagnetic interference (EMI) shielding, and thermal conductivity is crucial for the application of highly integrated miniaturized electronic devices.

[0003] Therefore, the prior art still needs to be improved and developed. Summary of the invention

[0004] Based on the above-mentioned deficiencies of the prior art, the object of the present invention is to provide a conductive and thermal conductive electromagnetic shielding composite material and a preparation method thereof, aiming to provide a material with good electrical conductivity, thermal conductivity and electromagnetic shielding performance.

[0005] The technical solution of the present invention is as follows:

[0006] A first aspect of the present invention provides a method for preparing an electrically conductive and thermally conductive electromagnetic shielding composite material, comprising the following steps:

[0007] Modifying the graphene nanosheets with a silane modifier to obtain silane-modified graphene nanosheets;

[0008] Adding the silane-modified graphene nanosheets, the first polymer material and the soluble particles into an organic solvent to obtain a mixed solution;

[0009] Placing the mixed liquid in a mold of a preset shape, and drying the mixed liquid to obtain a material of a preset shape;

[0010] Placing the material having the preset shape in a hot water bath for washing to obtain a three-dimensional porous material;

[0011] Infusing a second polymer material into the pores of the three-dimensional porous material, and after curing, obtaining an electrically conductive, thermally conductive, and electromagnetic shielding composite material;

[0012] The soluble particles are soluble in water but insoluble in the organic solvent.

[0013] Optionally, the method for preparing the silane-modified graphene nanosheets comprises the following steps:

[0014] Providing a graphene nanosheet dispersion;

[0015] The silane modifier is added to the graphene nanosheet dispersion, stirred at 70° C. for 1 to 4 hours, centrifuged, washed and dried to obtain the silane-modified graphene nanosheet.

[0016] Optionally, the silane modifier includes at least one of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane.

[0017] Optionally, the organic solvent includes at least one of 1,4-dioxane, tetrahydrofuran, acetone, ethyl acetate, dimethyl sulfoxide, benzene and toluene.

[0018] Optionally, the particle size of the soluble particles is 20 to 300 μm;

[0019] And / or, the soluble particles include at least one of sodium chloride, potassium chloride, calcium chloride, sucrose, sodium bicarbonate and sodium carbonate.

[0020] Optionally, the first polymer material includes at least one of polyvinylidene fluoride, polyetheretherketone, thermoplastic polyurethane rubber and polymethyl methacrylate.

[0021] Optionally, the second polymer material includes at least one of a silicone-based rubber material, an epoxy resin, and a hydrogenated styrene-butadiene block copolymer; the silicone-based rubber material includes at least one of Ecoflex, polydimethylsiloxane, liquid silicone rubber, polydiphenylsiloxane, and methacryloyloxypropyltrimethoxysilane.

[0022] Optionally, the perfusion is vacuum perfusion, and the perfusion time is 1 to 3 hours.

[0023] Optionally, the ratio of the silane-modified graphene nanosheets, the first polymer material, the soluble particles and the organic solvent is (1-5) g: (1-5) g: (10-50) g: (10-50) mL;

[0024] The ratio of the mass of the silane-modified graphene nanosheet to the sum of the mass of the first polymer material and the second polymer material is (0-20):(80-100), and the mass of the silane-modified graphene nanosheet is not zero.

[0025] A second aspect of the present invention provides an electrically conductive and thermally conductive electromagnetic shielding composite material, wherein the electrically conductive and thermally conductive electromagnetic shielding composite material is prepared by the preparation method of the present invention as described above.

[0026] Beneficial effects: The conductive, thermally conductive and electromagnetic shielding composite material provided by the present invention has good electrical conductivity, thermal conductivity and electromagnetic shielding performance, and has the effect of isotropic thermal conductivity, can effectively perform heat transfer and electromagnetic shielding, and can be applied to electronic equipment to reduce the heat generated during the operation of the electronic equipment and effectively avoid electromagnetic interference, thereby improving the stability of the operation of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The stability test results of the silane-modified graphene nanosheet dispersion and the ordinary graphene nanosheet dispersion in Example 1, wherein (a) is before the test, and (b) is after standing for 48 hours.

[0028] Figure 2 This is the SEM image of the three-dimensional porous material in Example 4.

[0029] Figure 3 This is a SEM image of the electrically conductive, thermally conductive, electromagnetic shielding composite material in Example 4.

[0030] Figure 4 This is a graph showing the electromagnetic interference shielding effectiveness results of the materials in Examples 1 to 4 and Comparative Example 9.

[0031] Figure 5 This is a graph showing the electrical conductivity results of the electrically conductive, thermally conductive, electromagnetic shielding composite materials in Examples 1 to 4. DETAILED DESCRIPTION

[0032] The present invention provides a conductive and thermal conductive electromagnetic shielding composite material and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0033] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0034] Although the incorporation of conductive fillers (metal particles, carbon nanotubes, graphene) into a polymer matrix to produce a conductive polymer composite material can simultaneously achieve electrical conductivity, thermal conductivity and electromagnetic shielding performance. However, the low interfacial bonding strength between graphene nanosheets and polymers and the agglomeration of graphene nanosheets make it difficult for graphene-based conductive polymer composites to achieve ideal electrical conductivity, thermal conductivity and electromagnetic shielding effects; in addition, conductive polymer composites with excellent electrical, thermal and electromagnetic shielding properties usually require the addition of a large amount of conductive fillers. When added in excess, the poor interfacial compatibility between these conductive fillers and the polymer matrix will adversely affect the mechanical properties and processability of the polymer composite. Therefore, how to achieve electrical conductivity, thermal conductivity and electromagnetic shielding performance with a low conductive filler loading is a huge challenge that needs to be solved. Based on this, the present invention provides a method for preparing a conductive, thermally conductive and electromagnetic shielding composite material, which includes the following steps:

[0035] S1, modifying the graphene nanosheets using a silane modifier to obtain silane-modified graphene nanosheets;

[0036] S2, adding the silane-modified graphene nanosheets, the first polymer material and the soluble particles into an organic solvent to obtain a mixed solution; placing the mixed solution in a mold of a preset shape, and after drying, obtaining a material with a preset shape; the soluble particles are soluble in water but insoluble in the organic solvent;

[0037] S3, placing the material having a preset shape in a hot water bath for washing to obtain a three-dimensional porous material;

[0038] S4. Infusing a second polymer material into the pores of the three-dimensional porous material, and after curing, obtaining a conductive, thermally conductive, electromagnetic shielding composite material (i.e., a conductive, thermally conductive, electromagnetic shielding composite material having a three-dimensional filler structure).

[0039] The conductive and thermal conductive electromagnetic shielding composite material provided by the present invention has good electrical conductivity, thermal conductivity and electromagnetic shielding performance, and has the effect of isotropic thermal conductivity, can effectively perform heat transfer and electromagnetic shielding, and can be applied to electronic equipment to reduce the heat generated during the operation of the electronic equipment and effectively avoid electromagnetic interference, thereby improving the stability of the operation of the electronic device.

[0040] The present invention firstly carries out surface modification modification to graphene nanosheets by silane modifiers, improves its dispersibility (avoiding its agglomeration) and interface compatibility, is conducive to the close combination of graphene nanosheets and the first polymer material and the second polymer material, reduces the generation of defects, realizes the desired electrical conduction, heat conduction and electromagnetic shielding effects, and can also reduce the usage amount of graphene nanosheets in addition. That is, there is enhanced interface compatibility between silane-modified graphene nanosheets and the first polymer material and the second polymer material, and this enhanced interface bonding reduces phonon scattering and interface resistance. Meanwhile, silane-modified graphene nanosheets and the first polymer material are more closely connected by electrostatic interaction or hydrogen bond, further optimizing the three-dimensional heat transfer network. In addition, silane modifier molecules can form a tighter network by hydrogen bond cross-linking graphene nanosheets, so that the interaction between silane-modified graphene nanosheets is also enhanced. Finally, the enhancement of the dispersibility of graphene nanosheets by silane modifiers also enhances the overall performance of composite materials as thermal interface materials. That is, the embodiments of the present invention can reduce interface defects, enhance coupling effects, improve interface contact, and enhance the performance of composite materials through filler (i.e., graphene nanosheet) modification.

[0041] Then, a mixed solution containing silane-modified graphene nanosheets, a first polymer material, soluble particles and an organic solvent is placed in a mold of a preset shape to obtain a material with a preset shape. Next, the material with a preset shape is placed in a hot water bath, and the soluble particles are used as a template to prepare a three-dimensional porous filler network. Due to the presence of a sufficient amount of soluble particles, gaps are formed in the material with a preset shape. Finally, in the hot water bath, hot water enters the material with a preset shape from the formed gaps, dissolving the soluble particles in water to achieve the purpose of removing the soluble particle template. Holes are left at the positions of the original soluble particles in the material with a preset shape, thereby obtaining a material with a rich and regular three-dimensional pore structure composed of silane-modified graphene nanosheets and the first polymer material (i.e., a three-dimensional porous material, which acts as a three-dimensional filler network in the conductive, thermal and electromagnetic shielding composite material finally prepared), and at the same time, the silane-modified graphene nanosheets in the three-dimensional porous material are stacked in parallel along the pore walls to form a continuous multi-oriented structure.

[0042] The present invention can not only reduce the amount of filler added by introducing a three-dimensional filler network, but also improve the electrical conductivity, thermal conductivity and electromagnetic shielding performance of the composite material. Specifically, the filler, i.e., silane-modified graphene nanosheets, forms a continuous conductive network in the composite material, which can not only provide an electron transmission path, impart electrical conductivity to the material, but also these conductive networks act as heat conduction paths, thereby enhancing thermal conductivity. At the same time, the multiple reflections, absorption and scattering of electromagnetic waves by these conductive networks contribute to effective electromagnetic shielding. The introduction of the three-dimensional filler network is further conducive to the rapid transmission of electrons, effectively transfers phonons, forms efficient heat conduction channels, and heat can be rapidly diffused and transferred along these channels, thereby improving the thermal conductivity of the composite material and increasing the electrical and thermal conductivity in all directions. The three-dimensional conductive network can also effectively reflect and absorb the incident electromagnetic waves, and the complex network architecture provides multiple scattering and reflection paths, prolongs the propagation path of the electromagnetic waves, and enhances the attenuation and dissipation of electromagnetic waves in the composite material, thereby significantly improving the electromagnetic shielding performance. Therefore, the present invention introduces a three-dimensional filler network to achieve excellent electrical conductivity, thermal conductivity and electromagnetic shielding effects at low filling loads. Specifically, high thermal conductivity, electrical conductivity and electromagnetic shielding performance are achieved at the same time at a low filling amount (9.78wt%), with the in-plane thermal conductivity reaching 9.86W / mK and the out-of-plane reaching 7.26W / mK; the electrical conductivity reaches 1560S / m; the electromagnetic shielding effectiveness reaches 78.6dB, meeting the requirements of aerospace equipment (60-90dB). In addition, the present invention provides soluble particles, which can be washed away by soaking in hot water. The method is simple and low in cost, and a regular porous structure is formed with controllable pore size, which is conducive to the subsequent infusion of the second polymer material. Compared with the traditional mixing method, the agglomeration of the filler is avoided and a more uniform distribution is achieved.

[0043] Finally, the second polymer material is infused into the pores of the three-dimensional porous material to serve as a supporting material and provide mechanical properties.

[0044] In step S1, in some embodiments, the method for preparing silane-modified graphene nanosheets comprises the following steps:

[0045] S11, providing a graphene nanosheet dispersion;

[0046] S12, adding a silane modifier to the graphene nanosheet dispersion, stirring at 70° C. for 1 to 4 hours, centrifuging, washing, and drying to obtain the silane-modified graphene nanosheet.

[0047] In step S11, the method for preparing the graphene nanosheet dispersion comprises the following steps:

[0048] dispersing graphene nanosheets in a mixed solvent to obtain a graphene nanosheet dispersion;

[0049] The mixed solvent includes ethanol and water, and the mass ratio of ethanol to water is 4:1.

[0050] The surface of graphene nanosheets is modified by silane modifiers to improve their dispersibility and interface compatibility, enhance the dispersibility of graphene nanosheets in the first polymer material, and enhance the interface bonding strength between the graphene nanosheets and the first polymer material, thereby improving the electrical conductivity, thermal conductivity and electromagnetic shielding properties of the composite material. In addition, the silane modifier molecules can cross-link the graphene sheets through hydrogen bonds to form a tighter network, so that the interaction between the graphene nanosheets is enhanced.

[0051] In some embodiments, the silane modifier includes at least one of γ-aminopropyltriethoxysilane (KH-550), γ-methacryloxypropyltrimethoxysilane (KH-570), vinyltrimethoxysilane (A-171), γ-mercaptopropyltriethoxysilane (KH-590) and γ-glycidoxypropyltrimethoxysilane (KH-560), but is not limited thereto.

[0052] In step S2, in some embodiments, the organic solvent includes at least one of 1,4-dioxane, tetrahydrofuran, acetone, ethyl acetate, dimethyl sulfoxide, benzene and toluene, but is not limited thereto.

[0053] In some embodiments, the particle size of the soluble particles is 20 to 300 μm, for example, it can be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 110 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm, 200 μm, 210 μm, 220 μm, 230 μm, 240 μm, 250 μm, 260 μm, 270 μm, 280 μm, 290 μm, 300 μm or any value in a numerical range consisting of two of the above numerical values ​​as endpoints.

[0054] In some embodiments, the soluble particles (ie, water-soluble particles) include at least one of sodium chloride, potassium chloride, calcium chloride, sucrose, sodium bicarbonate, and sodium carbonate, but are not limited thereto.

[0055] In some embodiments, the first polymer material includes at least one of polyvinylidene fluoride (PVDF), polyetheretherketone (PEEK), thermoplastic polyurethane (TPU), and polymethyl methacrylate (PMMA), but is not limited thereto.

[0056] In some embodiments, the ratio of the silane-modified graphene nanosheets, the first polymer material, the soluble particles and the organic solvent is (1-5) g: (1-5) g: (10-50) g: (10-50) mL. For example, it can be 1 g: 1 g: 10 g: 10 mL, 1 g: 1 g: 50 g: 50 mL, 5 g: 1 g: 20 g: 30 mL, 1 g: 5 g: 10 g: 50 mL or 2.5 g: 3 g: 20 g: 30 mL, etc.

[0057] In step S3, the material having a preset shape (such as a square, a cylinder, etc., which can be selected according to actual needs) is placed in a hot water bath, and the soluble particles are continuously dissolved in the hot water bath to achieve cleaning, and the soluble particles are removed to form a three-dimensional porous material. In some embodiments, the temperature of the hot water bath is 60° C., and the cleaning time is 3 hours.

[0058] In step S4, the second polymer material is poured into the pores of the three-dimensional porous material. If the second polymer material is in liquid form, the second polymer material is directly poured into the pores of the three-dimensional porous material. If the second polymer material is in solid form (such as powder form), the second polymer material is poured into the pores of the three-dimensional porous material in the form of a solution.

[0059] In some embodiments, the perfusion is vacuum perfusion (i.e., the second polymer material is perfused into the pores of the three-dimensional porous material under a vacuum environment), and the perfusion time is 1 to 3 hours (eg, 1 hour, 1.5 hours, 2 hours, 2.4 hours or 3 hours, etc.).

[0060] In some embodiments, the second polymer material includes at least one of a silicone-based rubber material, an epoxy resin, and a hydrogenated styrene-butadiene block copolymer (SEBS), but is not limited thereto; the silicone-based rubber material includes at least one of Ecoflex (specifically Ecoflex-00-30 silicone rubber, which is produced by Smooth-on, USA), polydimethylsiloxane (PDMS), liquid silicone rubber (LSR), polydiphenylsiloxane (PDPS), and methacryloyloxypropyltrimethoxysilane (PMHS), but is not limited thereto.

[0061] In steps S2 and S4, the ratio of the mass of the silane-modified graphene nanosheets to the sum of the mass of the first polymer material and the second polymer material is (0-20):(80-100), and the mass of the silane-modified graphene nanosheets is not 0. For example, the ratio of the mass of the silane-modified graphene nanosheets to the sum of the mass of the first polymer material and the second polymer material is 1:99, 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, 9:91, 10:90, 12:88, 15:85, 17:83, 20:80, 20:90 or 20:100, etc.

[0062] That is to say, the mass ratio of the first polymer material to the second polymer material and to the silane-modified graphene nanosheets is (80-100):(0-20), for example, it can be 80:20, 80:1, 99:1, 98:2, 97:3, 96:4 or 95:5, etc.

[0063] The embodiment of the present invention provides a conductive and thermally conductive electromagnetic shielding composite material, wherein the conductive and thermally conductive electromagnetic shielding composite material is prepared by the preparation method described in the embodiment of the present invention. The conductive and thermally conductive electromagnetic shielding composite material includes a three-dimensional porous material and a second polymer material filled in the three-dimensional porous material, and the three-dimensional porous material is composed of a first polymer material and silane-modified graphene nanosheets (that is, the pore wall frame of the three-dimensional porous material is composed of a first polymer material and silane-modified graphene nanosheets). The conductive and thermally conductive electromagnetic shielding composite material has good electrical conductivity, thermal conductivity and electromagnetic shielding properties. High thermal conductivity and electromagnetic shielding performance are achieved at the same time at a low filling amount (9.78wt%, the content of silane-modified graphene nanosheets in the composite material), the in-plane thermal conductivity reaches 9.86W / mK, and the out-of-plane thermal conductivity reaches 7.26W / mK, which is much higher than pure PDMS (0.154W / mK). The electromagnetic shielding effectiveness reaches 78.6dB, meeting the requirements of aerospace equipment (60-90dB).

[0064] The present invention will be further described below by means of specific examples.

[0065] Example 1

[0066] This embodiment provides a method for preparing a conductive and thermal conductive electromagnetic shielding composite material, comprising the following steps:

[0067] (1) Preparation of silane-modified graphene nanosheets

[0068] 5 g of graphene nanosheets were dispersed in 50 mL of a mixed solvent (composed of anhydrous ethanol and deionized water, with a mass ratio of anhydrous ethanol to deionized water of 4:1) and ultrasonicated for 2 hours to uniformly disperse them to form a graphene nanosheet dispersion.

[0069] 1 g of KH-550 was added to the above graphene nanosheet dispersion and stirred at 70°C for 4 h. Then, it was centrifuged and washed with ethanol and deionized water for 3 times. Finally, it was freeze-dried to obtain silane-modified graphene nanosheets.

[0070] (2) Preparation of three-dimensional porous materials

[0071] 1g of silane-modified graphene nanosheets was ultrasonically dispersed (time for 1h) in 10mL of acetone, and then 5g of PVDF was added and heated to 50°C to dissolve it. Then, 50g of sodium chloride particles (particle size of 300μm) were added and stirred vigorously to make it uniform to obtain a mixed solution; the mixed solution was poured into a square polytetrafluoroethylene mold and dried at 50°C for 6h to obtain a square block material;

[0072] The square block material is placed in 60°C water and allowed to stand for 3 hours to wash away the sodium chloride particles, thereby obtaining a three-dimensional porous material;

[0073] The three-dimensional porous material is placed in uncured PDMS (liquid) under a vacuum environment for infiltration and infusion, and then the infused material is cured at 60°C for 12 hours to obtain a conductive, thermally conductive, electromagnetic shielding composite material with a three-dimensional filler structure, which contains 1g of silane-modified graphene nanosheets, 5g of PVDF and 27g of PDMS.

[0074] Example 2

[0075] This embodiment provides a method for preparing a conductive and thermally conductive electromagnetic shielding composite material, which differs from Embodiment 1 only in that:

[0076] The amount of silane-modified graphene nanosheets used in step (2) is 2 g. The obtained conductive, thermally conductive, and electromagnetic shielding composite material contains 2 g of silane-modified graphene nanosheets, 5 g of PVDF, and 26 g of PDMS.

[0077] Example 3

[0078] This embodiment provides a method for preparing a conductive and thermally conductive electromagnetic shielding composite material, which differs from Embodiment 1 only in that:

[0079] The amount of silane-modified graphene nanosheets used in step (2) is 3 g. The obtained conductive, thermally conductive, and electromagnetic shielding composite material contains 3 g of silane-modified graphene nanosheets, 5 g of PVDF, and 25 g of PDMS.

[0080] Example 4

[0081] This embodiment provides a method for preparing a conductive and thermally conductive electromagnetic shielding composite material, which differs from Embodiment 1 only in that:

[0082] The amount of silane-modified graphene nanosheets used in step (2) is 4 g. The obtained conductive, thermally conductive, and electromagnetic shielding composite material contains 4 g of silane-modified graphene nanosheets, 5 g of PVDF, and 31.9 g of PDMS.

[0083] Comparative Example 1

[0084] This comparative example provides a method for preparing a composite material, which differs from Example 1 only in that:

[0085] Step (1) was not performed, and in step (2), the silane-modified graphene nanosheets in Example 1 were replaced by graphene nanosheets in an amount of 1 g.

[0086] Comparative Example 2

[0087] This comparative example provides a method for preparing a composite material, which differs from Example 2 only in that:

[0088] Step (1) was not performed, and in step (2), the silane-modified graphene nanosheets in Example 2 were replaced by graphene nanosheets, and the amount of graphene nanosheets used was 2 g.

[0089] Comparative Example 3

[0090] This comparative example provides a method for preparing a composite material, which differs from Example 3 only in that:

[0091] Step (1) was not performed, and in step (2), the silane-modified graphene nanosheets in Example 3 were replaced by graphene nanosheets, and the amount of graphene nanosheets used was 3 g.

[0092] Comparative Example 4

[0093] This comparative example provides a method for preparing a composite material, which differs from Example 4 only in that:

[0094] Step (1) was not performed, and in step (2), the silane-modified graphene nanosheets in Example 4 were replaced by graphene nanosheets, and the amount of graphene nanosheets used was 4 g.

[0095] Comparative Example 5

[0096] This comparative example provides a method for preparing a composite material, comprising the following steps:

[0097] 1 g of graphene nanosheets and 32 g of PDMS (liquid) were stirred evenly, and cured at 60° C. for 12 h to obtain a composite material (i.e., a graphene / PDMS direct blended composite material).

[0098] Comparative Example 6

[0099] This comparative example provides a method for preparing a composite material, which differs from comparative example 5 only in that:

[0100] The amount of graphene nanosheets used was 2.04 g.

[0101] Comparative Example 7

[0102] This comparative example provides a method for preparing a composite material, which differs from comparative example 5 only in that:

[0103] The amount of graphene nanosheets used was 3.16 g.

[0104] Comparative Example 8

[0105] This comparative example provides a method for preparing a composite material, which differs from comparative example 5 only in that:

[0106] The amount of graphene nanosheets used was 3.47 g.

[0107] Comparative Example 9

[0108] This comparative example provides a method for preparing a pure PMDS material, comprising the following steps:

[0109] 32 g of PVDF was added to 100 mL of acetone, and the temperature was raised to 50° C. to dissolve the PVDF in acetone to obtain a mixed solution; the mixed solution was poured into a square polytetrafluoroethylene mold, and cured at 60° C. for 12 hours to obtain pure PVDF material.

[0110] test:

[0111] (1) The dispersion of the silane-modified graphene nanosheets prepared in Example 1 and the dispersion of the common graphene nanosheets (i.e., the graphene nanosheets not modified by silane) were allowed to stand for 48 hours and then observed. The results are as follows: Figure 1 As shown (where GNP is a common graphene nanosheet dispersion and mGNP is a silane-modified graphene nanosheet dispersion), it can be found that the common graphene nanosheet dispersion is stratified, while the silane-modified graphene nanosheet dispersion prepared in Example 1 has good dispersibility and stability and does not show stratification.

[0112] (2) The scanning electron microscope (SEM) image of the three-dimensional porous material in Example 4 is as follows Figure 2 As shown, it can be seen that the material is a three-dimensional porous structure, which proves the successful preparation of the three-dimensional porous material.

[0113] (3) The SEM image of the cross section of the conductive and thermal conductive electromagnetic shielding composite material prepared in Example 4 is as follows: Figure 3 As shown in the figure, the red dotted line represents the three-dimensional porous material framework, which is the main path for electrical and thermal conduction. The yellow arrow area is the PDMS material filled in.

[0114] (4) The materials in Examples 1 to 4 and Comparative Examples 1 to 9 were tested for in-plane thermal conductivity, out-of-plane thermal conductivity and electromagnetic shielding performance. The results are shown in Table 1. Figure 4 and Figure 5 shown.

[0115] Table 1. Results of in-plane thermal conductivity test, out-of-plane thermal conductivity test and electromagnetic interference shielding effectiveness test

[0116] sample In-plane thermal conductivity (W / mK) Out-of-plane thermal conductivity (W / mK) Electromagnetic shielding (dB) Example 1 1.572 1.272 32.4 Example 2 3.898 2.578 39.2 Example 3 6.382 4.562 52.1 Example 4 9.864 7.264 78.1 Comparative Example 1 1.223 0.533 22.5 Comparative Example 2 2.582 1.223 27.9 Comparative Example 3 4.292 2.692 49.3 Comparative Example 4 6.962 4.686 67.9 Comparative Example 5 0.227 0.127 13.2 Comparative Example 6 0.302 0.124 15.9 Comparative Example 7 0.532 0.133 22.6 Comparative Example 8 0.974 0.169 27.8 Comparative Example 9 0.154 0.121 3.1

[0117] Figure 4 In the EMI SE, it means electromagnetic interference shielding effectiveness. R is the reflective shielding effectiveness, SE A To absorb shielding effectiveness, SE T is the total shielding effectiveness. Among them, the SE of the pure PMDS material in Comparative Example 9 R , SE A and SE T 0.7dB, 2.4dB and 3.1dB respectively. The SE of the conductive and thermal conductive electromagnetic shielding composite material in Example 1 is R , SE A and SE T 5.0dB, 27.4dB and 32.4dB respectively. The SE of the conductive and thermal conductive electromagnetic shielding composite material in Example 2 is R , SE A and SE T 7.1dB, 32.2dB and 39.2dB respectively. The SE of the conductive and thermal conductive electromagnetic shielding composite material in Example 3 is R , SE A and SE T 8.6dB, 43.5dB and 52.1dB respectively. The SE of the conductive and thermal conductive electromagnetic shielding composite material in Example 4 is R , SE A and SE T They are 12.2dB, 65.9dB and 78.1dB respectively.

[0118] Depend on Figure 5 It can be seen that the electrical conductivities of the electrically conductive, thermally conductive, and electromagnetic shielding composite materials in Example 1, Example 2, Example 3, and Example 4 are 2.5 S / m, 219.2 S / m, 1030.9 S / m, and 1560 S / m, respectively.

[0119] It can be seen that the composite material provided by the present invention has good electrical conductivity, thermal conductivity and electromagnetic shielding properties. Compared with simple random mixing (Comparative Examples 5-8), the present invention introduces fillers (silane-modified graphene nanosheets) into the second polymer material in the form of a three-dimensional network to enhance the physical contact between filler particles, thereby forming a continuous electrical and thermal conductivity path. These approaches greatly reduce the heat transfer resistance across the material interface, while minimizing phonon scattering, thereby improving thermal conductivity and diffusivity. In addition, from the comparison of Examples 1-4 with Comparative Examples 1-4, it can be found that the electrical conductivity, thermal conductivity and electromagnetic shielding properties of the composite material can be improved by modifying the graphene nanosheets. In addition, the present invention can still achieve good electrical conductivity, thermal conductivity and electromagnetic shielding properties under the premise of a lower loading amount of fillers.

[0120] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing an electrically conductive and thermally conductive electromagnetic shielding composite material, characterized in that: The steps include: Modifying the graphene nanosheets with a silane modifier to obtain silane-modified graphene nanosheets; Adding the silane-modified graphene nanosheets, the first polymer material and the soluble particles into an organic solvent to obtain a mixed solution; Placing the mixed liquid in a mold of a preset shape, and drying the mixed liquid to obtain a material of a preset shape; Placing the material having the preset shape in a hot water bath for washing to obtain a three-dimensional porous material; Infusing a second polymer material into the pores of the three-dimensional porous material, and after curing, obtaining an electrically conductive, thermally conductive, and electromagnetic shielding composite material; The soluble particles are soluble in water but insoluble in the organic solvent.

2. The preparation method according to claim 1, characterized in that: The preparation method of the silane-modified graphene nanosheets comprises the following steps: Providing a graphene nanosheet dispersion; The silane modifier is added to the graphene nanosheet dispersion, stirred at 70° C. for 1 to 4 hours, centrifuged, washed and dried to obtain the silane-modified graphene nanosheet.

3. The preparation method according to claim 2, characterized in that: The silane modifier includes at least one of γ-aminopropyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, γ-mercaptopropyltriethoxysilane and γ-glycidoxypropyltrimethoxysilane.

4. The preparation method according to claim 1, characterized in that: The organic solvent includes at least one of 1,4-dioxane, tetrahydrofuran, acetone, ethyl acetate, dimethyl sulfoxide, benzene and toluene.

5. The preparation method according to claim 1, characterized in that: The particle size of the soluble particles is 20 to 300 μm; And / or, the soluble particles include at least one of sodium chloride, potassium chloride, calcium chloride, sucrose, sodium bicarbonate and sodium carbonate.

6. The preparation method according to claim 1, characterized in that: The first polymer material includes at least one of polyvinylidene fluoride, polyetheretherketone, thermoplastic polyurethane rubber and polymethyl methacrylate.

7. The preparation method according to claim 1, characterized in that: The second polymer material includes at least one of a silicone-based rubber material, an epoxy resin, and a hydrogenated styrene-butadiene block copolymer; the silicone-based rubber material includes at least one of Ecoflex, polydimethylsiloxane, liquid silicone rubber, polydiphenylsiloxane, and methacryloyloxypropyltrimethoxysilane.

8. The preparation method according to claim 1, characterized in that: The perfusion is vacuum perfusion, and the perfusion time is 1 to 3 hours.

9. The preparation method according to claim 1, characterized in that: The ratio of the silane-modified graphene nanosheets, the first polymer material, the soluble particles and the organic solvent is (1-5) g: (1-5) g: (10-50) g: (10-50) mL; The ratio of the mass of the silane-modified graphene nanosheet to the sum of the mass of the first polymer material and the second polymer material is (0-20):(80-100), and the mass of the silane-modified graphene nanosheet is not zero.

10. An electrically conductive and thermally conductive electromagnetic shielding composite material, characterized in that: The electrically conductive, thermally conductive, electromagnetic shielding composite material is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of silicone rubber composite insulating material with excellent mechanical properties

    CN111944318A

  • Thermoelectric device based on high-elasticity compressible graphene / organic composite foam and preparation method thereof

    CN114005928A

  • Preparation method of epoxy resin-based composite material for electromagnetic shielding and heat conduction

    CN118290896A

Cited By

  • High thermal conductivity and electromagnetic shielding composite material and preparation method thereof

    CN122751546A